The Elgar dictionary of economic quotations - McCann, Charles Robert (Cheltenham, UK ; Northhampton, MA, USA : Edward Elgar Pub., 2003)
It is a collection of quotations by economists and other topics of specific interest to economists. A dictionary of quotations picks different authors of economic books and their resonating words.
"This collection ... was initiated by a suggestion of Edward Elgar at the January 2001 meeting of the American Economic Association in New Orleans"--T.p. verso.
Includes index.
Includes bibliographical references: p. 223-248.
sju 25/03/2019
Ref.
Keywords: Elgar, Edward; Economics; Economists